Significance of C-terminal cysteine modifications to the biological activity of the Saccharomyces cerevisiae a-factor mating pheromone. - Marcus, S (1991)
We have undertaken total synthesis of the Saccharomyces cerevisiae a-factor (NH2-YIIKGVFWDPAC[S-farnesyl]-COOCH3) and several Cys-12 analogs to determine the significance of S-farnesylation and carboxy-terminal methyl esterification to the biological activity of this lipopeptide mating pheromone. Replacement of either the farnesyl group or the carboxy-terminal methyl ester by a hydrogen atom resulted in marked reduction but not total loss of bioactivity as measured by a variety of assays. Moreover, both the farnesyl and methyl ester groups could be replaced by other substituents to produce biologically active analogs. The bioactivity of a-factor decreased as the number of prenyl units on the cysteine sulfur decreased from three to one, and an a-factor analog having the S-farnesyl group replaced by an S-hexadecanyl group was more active than an S-methyl a-factor analog. Thus, with two types of modifications, a-factor activity increased as the S-alkyl group became bulkier and more hydrophobic. MATa cells having deletions of the a-factor structural genes (mfal1 mfa2 mutants) were capable of mating with either sst2 or wild-type MAT alpha cells in the presence of exogenous a-factor, indicating that it is not absolutely essential for MATa cells to actively produce a-factor in order to mate. Various a-factor analogs were found to partially restore mating to these strains as well, and their relative activities in the mating restoration assay were similar to their activities in the other assays used in this study. Mating was not restored by addition of exogenous a-factor to a cross of a wild-type MAT alpha strain and a MATaste6 mutant, indicating a role of the STE6 gene product in mating in addition to its secretion of a-factor.